2020
DOI: 10.1101/2020.10.11.333047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the spatial signal of environmental DNA in river systems using a community ecology approach

Abstract: Environmental DNA (eDNA) is gaining a growing popularity among scientists but its applicability to biodiversity research and management remain limited in river systems by the lack of knowledge about the spatial extent of the downstream transport of eDNA. Up to now, attempts to measure eDNA detection distance compared known species distributions to eDNA results, limiting therefore studies to a few intensively studied rivers. Here we developed a framework to measure the detection distance of eDNA in rivers based… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…This observation is in agreement with what is yet documented in literature and summarized in Figure 7, showing that with high discharge rates, eDNA is detected over larger distances regardless of its concentration. Similar observations are also made using community‐based eDNA methods like metabarcoding, as reported by Laporte et al (2021), who found, for instance, that in a river system with a discharge rate of 16,800m 3 s −1 (in comparison to 1.41 ± 0.39m 3 s −1 in our downstream section), brown trout ( Salmo trutta ) was still detected up to 5 km downstream of the shedding source, although its relative abundance decreased to marginal levels (<1.0%) already after 100 m. This suggests that even in medium to large‐scale lotic systems (Cantera et al, 2022; Laporte et al, 2022) local assessment of fish communities might be possible, while the maintained detection at large distances allows biodiversity assessment at basin scale.…”
Section: Discussionmentioning
confidence: 41%
“…This observation is in agreement with what is yet documented in literature and summarized in Figure 7, showing that with high discharge rates, eDNA is detected over larger distances regardless of its concentration. Similar observations are also made using community‐based eDNA methods like metabarcoding, as reported by Laporte et al (2021), who found, for instance, that in a river system with a discharge rate of 16,800m 3 s −1 (in comparison to 1.41 ± 0.39m 3 s −1 in our downstream section), brown trout ( Salmo trutta ) was still detected up to 5 km downstream of the shedding source, although its relative abundance decreased to marginal levels (<1.0%) already after 100 m. This suggests that even in medium to large‐scale lotic systems (Cantera et al, 2022; Laporte et al, 2022) local assessment of fish communities might be possible, while the maintained detection at large distances allows biodiversity assessment at basin scale.…”
Section: Discussionmentioning
confidence: 41%
“…The performance of the ‘teleo’ primer pair has been investigated by Polanco et al (2021), who showed that it can efficiently discriminate fish species of the Maroni River, the river with the highest species richness in French Guiana. The ‘teleo’ primer has thus been used in previous studies focused on French Guianese fish fauna (Cantera, Coutant, et al, 2022; Cantera, Decotte, et al, 2022; Cantera et al, 2019; Cilleros et al, 2019). The DNA amplifications were performed in a final volume of 25 μl containing 1 U AmpliTaq Gold DNA Polymerase (Applied Biosystems), 0.2 μM of each primer, 10 mM Tris‐HCl, 50 mM KCl, 2.5 mM MgCl 2 , 0.2 mM of each dNTP and 3 μl DNA template.…”
Section: Methodsmentioning
confidence: 99%
“…Compared to those stream distances, fish eDNA dispersion distances in rivers span a much wider range—from 2 to 3 km for eDNA of fish assemblages in a small river (Civade et al, 2016) to up to 130 km for eDNA of the abundant whitefish (a species inhabiting Lake Geneva) downstream in the Rhône River (Pont et al, 2018). Therefore, eDNA‐sampled lotic biodiversity may represent a larger space than the classical catch‐based surveys, especially in large rivers (Pont et al, 2018; but see Cantera et al, 2022). Although in some cases eDNA may have long‐distance transport, results from a recent meta‐analysis, which employed a hydrodynamic modelling approach, suggest that most eDNA particles could travel less than 2 km downstream under normal conditions (Jo & Yamanaka, 2022).…”
Section: Often Asked Questions About Edna‐based Surveysmentioning
confidence: 99%
“…Despite a myriad of factors complicating the correlation between an eDNA source and its site of detection in a lotic system, many studies have demonstrated the capacity of eDNA analysis to Cantera et al (2022) showed that eDNA samples provided spatial patterns (decay of similarity between communities with increasing distance between sampling sites) comparable to those of local samples obtained with gill-netting in two large and species-rich neotropical rivers, thus testifying to local detection of species assemblages with eDNA. Therefore, the eDNA approach, appropriately applied in lotic systems, has the capacity to discriminate local spatial patterns at the community level.…”
Section: What Is the Spatial Representation Of Edna?mentioning
confidence: 99%